2005
DOI: 10.1253/circj.69.730
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Function and Morphology of Tumor Necrosis Factor-.ALPHA. Treated Endothelial Cells With 17-.BETA. Estradiol A Preliminary Study for a Feasible Simple Model for Atherosclerosis

Abstract: n normal vasculature endothelial cells (EC), a small amount of NO synthesized by endothelial nitric oxide synthase (eNOS) maintains normal vascular physiological function controls. 1,2 Endothelial cell dysfunction in eNOS expression by tumor necrosis factor-(TNF-) is involved in the pathogenesis of vascular diseases, for example atherosclerosis. 3 The related pathologic changes are increased expression of adhesion molecules, including intercellular adhesion molecule (ICAM)-1, vascular adhesion molecule (VCAM)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…18 E2 protects the endothelium by upregulating endothelial nitric oxide synthase and can reverse endothelial dysfunction in an in vitro vascular model. 19 In the present study we did not measure estrogen or other hormonal levels so we could not examine the correlation between E2 and FMD. In pregnancy the naturally occurring increase in E2 seems to protect the endothelium against the adverse lipid changes.…”
Section: Discussionmentioning
confidence: 87%
“…18 E2 protects the endothelium by upregulating endothelial nitric oxide synthase and can reverse endothelial dysfunction in an in vitro vascular model. 19 In the present study we did not measure estrogen or other hormonal levels so we could not examine the correlation between E2 and FMD. In pregnancy the naturally occurring increase in E2 seems to protect the endothelium against the adverse lipid changes.…”
Section: Discussionmentioning
confidence: 87%
“…15 Cevic et al demonstrated that a high concentration of estrogen reduces the level of asymmetric dimethylarginine (ADMA), which is an endogenous competitive inhibitor of nitric oxide (NO) synthase. 16 Estradiol, by reducing ADMA, may therefore facilitate NO synthesis in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 ECs apparently have to physically uncouple in order to allow transendothelial migration of leukocytes. Inflammatory mediators, such as tumor necrosis factor- 12,26 and lipopolysaccharide, 27 induce leukocyte adhesion molecules such as VCAM-1, but also downregulate connexin37 expression in vascular ECs. 28,29 The inhibition of connexin37 expression by CB thus seems to be associated with EC inflammatory process such as adhesion and/or transmigration of leukocytes.…”
Section: Discussionmentioning
confidence: 99%